(3QSGdI aj GdfMhs - (3YHO Gddg Hf Rjf GdOjf Hf CMeO Hf eMeO, GHf Ndjd GdHUQhj,J (B1170 (3g` s
(3ChdgG (B:s
(3hHYO, aEf GdTjNjf GdaGVdjf GdYdGeI YHOGdQMje, hGdagGeI MSf bO JLGQAG eQI aj ejOGf GdYdhe s
(3BNQgG (B:s
(3haj bhdg(B: (3hLYdgG YGeI Hbhdg hGdHGbj eG dG jNai bGd Pdc hcJHg abjQ Yah QHg YHOGddg Hf Rjf GdOjf GdHUQhj GdTGaYj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B32 - (3U(B37s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B56s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B140 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdfMhs